2016
DOI: 10.1515/lpts-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Synchronous Reluctance Motor Design

Abstract: The paper focuses on studying the external-rotor synchronous reluctance motor. The analysis is performed to estimate the influence of the number of stator slots and non-magnetic areas in the rotor (i.e., flux barriers) on the electromagnetic torque and torque ripple of the studied motor. It is concluded that the increase in the number of stator slots Z = 6 to Z = 18 causes an approximately twofold decrease in the ripple factor, but torque increases by 5 %. Electromagnetic torque will be increased approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The following sizes of the motor under analysis are taken as constant: the outer diameter is 170 mm, the axial length of the motor active part is 100 mm, the anchor outer diameter is 100 mm and air gap is 0.5 mm. The results presented in [7] show that the effective number of stator slots for the motor with the accepted dimensions is Z = 18. Larger slot number is no desirable from the perspective of dental mechanical strength and winding creation.…”
Section: Simulation Of Magnetic Field Of the Studied Motor And Resultmentioning
confidence: 97%
See 3 more Smart Citations
“…The following sizes of the motor under analysis are taken as constant: the outer diameter is 170 mm, the axial length of the motor active part is 100 mm, the anchor outer diameter is 100 mm and air gap is 0.5 mm. The results presented in [7] show that the effective number of stator slots for the motor with the accepted dimensions is Z = 18. Larger slot number is no desirable from the perspective of dental mechanical strength and winding creation.…”
Section: Simulation Of Magnetic Field Of the Studied Motor And Resultmentioning
confidence: 97%
“…According to the results obtained in paper [7], it has been concluded that after increasing the number of stator slots, torque ripple is substantially reduced, while an amplitude value of the fundamental harmonic of electromagnetic torque is slightly increased. Thus, increasing the number of stator slots from Z = 6 to Z = 18 leads to an approximately twofold decrease in the torque ripple factor and to an increase in the amplitude value of fundamental harmonic of electromagnetic torque by 5 %.…”
Section: Analysis Of Rotor Designs For Synchronous Reluctance Motormentioning
confidence: 87%
See 2 more Smart Citations
“…T 1max -the amplitude of the first harmonic of electromagnetic torque curve; 3. k p -the ripple factor. For calculation of ripple factor k p formula from [10] is used (2) where n is the number of evenly selected points on the half interval of the electromagnetic torque sinusoidal curve; Δa is the difference between values of the electromagnetic torque T em and the first harmonic of electromagnetic torque T em1 in relevant points; T max1 is the maximum of the first harmonic of electromagnetic torque. Table 2 and shown in Fig.…”
Section: Magnetic Field Simulations and Results Analysismentioning
confidence: 99%